Your first million : why you don't have to be born into a legacy of wealth to leave one behind : an entrepreneur's guide - Hamilton, Arlan; Nelson, Rachel L. (Little, Brown Spark, 2024)
"Having lived nearly her entire life below the poverty line before going on to attain wealth and success as an entrepreneur and investor, Arlan Hamilton knows that entrepreneurship is the quickest path to money and power-particularly for those who haven't had much of it in the past. In Your First Million, she shows how anyone-no matter what they look like or how much money they have-can tap into all the new tools they already have at their disposal to get their million-dollar idea off the ground. Readers will learn: how to identify unmet needs, raise money, choose the right collaborators, create multiple income streams, and turn their unique knowledge and experience into a profitable businesses-while reinvesting in their communities and empowering others to do the same. If we can change who gets to decide what new ideas are worthy, and who gets to turn those ideas into reality, not only can we change our own circumstances-we can change the world"--